Manajemen Pasien Leptospirosis di ICU - Jufan, Akhmad Yun; Widodo, Untung; Bahrun, Nugraha Septian (Jurnal Komplikasi Anestesi, 2021)
We reported a 54-year-old male patient with leptospirosis, septic shock, and MODS. Patient is referred from RSUD Prambanan with chief complaint of high fever accompanied by yellow eyes and body, headache, calf pain, body aches rheumatic pain, nausea, vomiting, shortness of breath, and tea colored urine. From history taking, it was found that there was a possibility of a history of contact with animals that were the source of transmission of leptospirosis, namely rats. The patient was treated in the ICU for several days. During treatment, hemodialysis was performed several times due to an increase in blood urea. After being treated for several days, the patient’s condition improved and treatment was carried out on the ward by internist.